Sources of Financing Public Passenger Transport Services - Milos Poliak; Lenka Komackova; Salvador Hernandez; Marek Jaskiewicz; Gabriela Boldizsarova (Communications - Scientific letters of the University of Zilina, 2017)
The paper deals with the financing of public passenger transport. It analyses unconventional types of financing public passenger transport abroad. The aim of the paper is to present the methodology of creating funding sources for the financing of public passenger transport which is applicable in the Slovak Republic and in the member states of the European Union. The key idea of the methodology is to use funding sources arising from the provision of public services.